2010
DOI: 10.1111/j.1478-3231.2009.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling and functional assays of activated hepatic stellate cells suggest that myocardin has a role in activation

Abstract: This study demonstrates that myocardin is involved in the activation of HSC; myocardin may serve as a novel therapeutic target in the treatment of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Not surprisingly, pathways related to cell-ECM interactions were dysregulated, such as extracellular region, ECM, and extracellular region part, confirming that the ECM plays a crucial role in regulating PSC phenotype. A similar study comparing gene expression patterns in human hepatic stellate cell lines cultured on plastic vs. Matrigel for 3 days has identified several dysregulated pathways, such as muscle development, cellular morphogenesis, organ development, and regulation of cell growth (27). These pathways were also found altered in the present study, which confirmed that stellate cells from different organs behave in a similar way when cultured on physiological or nonphysiological activating matrices.…”
Section: Discussionsupporting
confidence: 92%
“…Not surprisingly, pathways related to cell-ECM interactions were dysregulated, such as extracellular region, ECM, and extracellular region part, confirming that the ECM plays a crucial role in regulating PSC phenotype. A similar study comparing gene expression patterns in human hepatic stellate cell lines cultured on plastic vs. Matrigel for 3 days has identified several dysregulated pathways, such as muscle development, cellular morphogenesis, organ development, and regulation of cell growth (27). These pathways were also found altered in the present study, which confirmed that stellate cells from different organs behave in a similar way when cultured on physiological or nonphysiological activating matrices.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between basement membrane-like matrix and the activation process of HSC has been the focus of considerable research. Friedman and many other researchers have shown that tissue culture dishes coated with Englebreth-Holm-Sarcoma-derived basement membrane-like matrix maintain HSC in a nonproliferative and non-fibrogenic status in vitro [8][9][10][11][12][13]. In our study, we demonstrate that primary rat HSC cultured on a NM retain a quiescent phenotype and that HSC activated by growth on PP revert toward a quiescent state when replated on NM.…”
Section: Discussionsupporting
confidence: 47%
“…Extensive studies have used this in vitro model to characterize the activated phenotype of HSC. By contrast, HSC retain a quiescent phenotype when cultured on a thick layer of basement membrane ECM and, furthermore, these basement membrane-like matrices can induce deactivation of HSC [8][9][10][11][12][13]. This three-dimensional (3D) in vitro ECM culture model resembles the tissue architecture in the perivascular space of Disse which surrounds HSC in a normal liver and supports the 3D cell structure and morphology of HSC in the quiescent state in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…Adult mice with one copy of Myocd showed lower bladder capacity consistent with a hypersensitive phenotype[159]. Hepatic stellate cells can undergo transdifferentiation to a myofibroblast-like phenotype in liver diseases associated with fibrosis, and studies have shown MYOCD is induced in experimental models of liver fibrosis[160],[161]. Interestingly, reducing MYOCD with siRNA predictably normalized the myofibroblast phenotype, suggesting that MYOCD (and probably its related MRTFs) could be a novel target for the treatment of liver fibrosis[161].…”
Section: Pathological Processes Linked To Myocardinmentioning
confidence: 99%